Transforming an Urban School System Progress of New Haven School Change and New Haven Promise Education Reforms (2010-2013)-Technical Appendixes - Scherer, Ethan (RAND Corporation, 2014)
In the 2010-2011 school year two educational programs launched in New Haven, Connecticut: New Haven School Change, a sweeping K-12 educational reform, and New Haven Promise, a scholarship program intended to encourage graduates to attend college. This volume contains the supporting appendixes for RAND's study of baseline conditions and early progress in these programs.